TKPKD DAN KEMISKINAN MASYARAKAT PEDESAAN - Samsul Samsul; Peribadi Peribadi; Muhammad Arsyad; Tanzil Tanzil; Juhaepa Juhaepa (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2022)
This study aims to describe the existence of the Regional Poverty Reduction Coordination Team (TKPKD) as a structural institution that greatly determines the success and failure of the Poverty Reduction Program (Pronangkis), especially those that arise in rural areas. For this reason, this research is directed at efforts to re-functionalize the TKPKD as a structural institution through a qualitative approach with a case study core. The results of the study show that several cases of very worrying poverty are experienced by rural communities in the South Konawe Regency Government area as a result of the dysfunctionalization of the TKPKD. Among them are the socio-economic portrait of stone-breaking women in Wawatu Village, Moramo District, the existence of homeless peasants in Mowila Village, Mowila District, marginalization of shifting cultivators in the wilderness of Wolasi District and the cries of fishermen on the coast with their various problems. Moving on from the narrative of rural community life, an institutional model is designed that can be used by local governments to activate TKPKD institutions to solve various problems of rural community life.